2012
DOI: 10.1111/j.1399-5618.2012.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential executive functioning performance by phase of bipolar disorder

Abstract: Objective This study examined the influence of illness phase on executive functioning performance using factor-derived cognitive scores in a cross-sectional design. Methods Healthy control (HC) subjects (n = 57), and euthymic (E-BD) (n = 117), depressed (D-BD) (n = 73), and hypomanic/mixed (HM/M-BD) (n = 26) patients with bipolar disorder (BD) were evaluated using executive functioning measures (Wisconsin Card Sorting Test, Trail Making Test–Parts A and B, Verbal Fluency, Parametric Go/No-Go, Stroop, and Dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 33 publications
5
61
0
7
Order By: Relevance
“…Although the slow antisaccade latencies in BD patients could be due to anticipation for saccade execution given a fixed and predictable preparation interval (1600 ms), it is unlikely as other studies that employed a non-predictable preparation interval documented similar findings (e.g., Katsanis et al, 1997). Furthermore, this pattern of data is also consistent with response time experiments in BD that reported inhibitory control deficits across mood states, including euthymia (Ryan et al, 2012;). To obtain the whole picture, we should note that in the latencies of the prosaccade task, euthymic patients were not slower than controls.…”
Section: Discussionsupporting
confidence: 73%
“…Although the slow antisaccade latencies in BD patients could be due to anticipation for saccade execution given a fixed and predictable preparation interval (1600 ms), it is unlikely as other studies that employed a non-predictable preparation interval documented similar findings (e.g., Katsanis et al, 1997). Furthermore, this pattern of data is also consistent with response time experiments in BD that reported inhibitory control deficits across mood states, including euthymia (Ryan et al, 2012;). To obtain the whole picture, we should note that in the latencies of the prosaccade task, euthymic patients were not slower than controls.…”
Section: Discussionsupporting
confidence: 73%
“…The apparent discrepancy between previous null effects when investigating the effect of psychopathy on response inhibition in the standard Go/No-go task (Kiehl et al, 2000;Verona et al, 2012) and the uncovered relationships when utilising the PGNG (Weidacker et al, 2017) supports the view that this task is more likely to capture aberrant response inhibition. There is evidence that it is the dynamic parametric approach of the PGNG and associated increased difficulty, which reveals response inhibition deficits previously unseen when using the standard Go/No-go task (Langenecker et al, 2010;Ryan et al, 2012). In terms of psychopathy for example, LaPierre et al (1995) reported a deficit in response inhibition performance in psychopathic offenders when utilizing a Go/No-go design, which incorporated a high demand on spatial attention by including a measure of uncertainty in the location of targets which appeared at pseudorandom locations.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of these design features has led to the PGNG capturing response inhibition deficits in, for example, bipolar disorder, where impulsivity is by definition part of the disorder (American Psychiatric Association, 2013), although response inhibition deficits had been unseen when utilising the standard Go/No-go task in bipolar patients (e.g. Elliott et al, 2004;Altshuler et al, 2005;Langenecker et al, 2010;Ryan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Durante as fases agudas do transtorno, pode haver exacerbação transitória de alguns déficits cognitivos como controle inibitório e fluência/aprendizado verbal (Ryan et al, 2012 (Senju, 2012;Bora;. Alguns autores propuseram que a cognição social poderia ser relativamente preservada no TB em comparação com a esquizofrenia (Lee et al, 2013).…”
Section: Funcionamento Neurocognitivo Nas Fases Agudas Do Transtorno unclassified
“…Assim, o padrão de comprometimento cognitivo observado aqui com a BNT em pacientes TB em relação ao CS é consistente com a literatura anterior, incluindo estudos que adotaram a (Van Rheenen e Rossell, 2014, Ishisaka et al, 2016, Bo et al, 2017 (Volkert et al, 2015). O impacto dos sintomas do humor na cognição foi avaliado principalmente por estudos e meta-análises comparando ou regredindo pacientes com TB de acordo com o estado de humor (ou seja, depressivo vs maníaco vs eutímico) (Kurtz e Gerraty, 2009;Ryan et al, 2012;Lee et al, 2014), mas, poucas investigações correlacionaram os sintomas de humor sub-sindrômicos em pacientes eutímicos com o com desempenho neurocognitivo.…”
Section: Validação De Critério Da Versão Em Português Da Penn-cnbunclassified